PERLINDUNGAN HUKUM BAGI PEMEGANG LISENSI HAK SIAR TERHADAP TAYANGAN STREAMINGTIDAK BERLISENSI - Susanto, Bima Yoga Shendy (JIPRO: Journal of Intellectual Property, 2022)
This study aims to answer whether the practice of unlicensed streaming violates the provisions of Law Number 28 of 2014 concerning Copyright and what legal remedies can be taken by holders of broadcast rights licenses against unlicensed streaming shows. This research is normative legal research using statutory and conceptual approaches. The results of this study conclude that the practice of unlicensed streaming is an act that violates the provisions of Law Number 28 of 2014 concerning Copyright. The legal remedy that can be taken by broadcasting rights license holders against unlicensed streaming shows is to make efforts to resolve disputes, namely through alternative dispute resolution, arbitration, or courts, the provisions of which are regulated in Chapter XIV concerning Dispute Resolution in Law Number 28 of 2014 concerning Copyright. In addition, broadcasting rights license holders can also file a cassation request as a legal remedy against the Commercial Court's decision.